PI de cultivares na Embrapa Tabuleiros Costeiros : estudo das relações de parceria / Sayonara Marinho Soares Borges - Borges, Sayonara Marinho Soares (2014)
Considering the legal and technical sceneries, which are favorable to the development of new cultivars: the founding of the National System for Cultivar Protection in the Department of Agriculture, Livestock and Food Supply (SNPC/MAPA), the Cultivar Protection Act (LPC), the Biosafety Act (LB), the Industrial Property Act (LPI), the Innovation Act (LI), the Seeds and Seedlings Act (LSM) and also the vegetable Genetic Improvement Program (PMGV), as well as the farming sector and market demand for technological solutions, this work aims at studying the partnership affairs between Brazilian Agricultural Research Corporation - Embrapa Coastal Tablelands and other Embrapa Units for the development of cultivars. As part of the methodology, the case study was divided into a quantitative and qualitative research, focusing mainly on looking into the number of registered cultivars as of the year in which the SNPC was founded until the latest cultivar jointly developed by Embrapa Coastal Tablelands and other Embrapa Units, presenting the scenario of cultivars placed on the market after the SNPC was founded and having a deeper look into the intellectual property (IP) status of those new materials. In order to complement the quantitative data, searches were carried out on the Embrapa Headquarters and Embrapa Products and Market´s websites, with the assistance of Embrapa´s Technological Business Secretariat. Moreover, interviews were conducted with Embrapa´s improvers and experienced cultivar IP technicians at Embrapa Products and Market in Petrolina/PE and Sete Lagoas/MG. The partnership affairs were matched up by means of bibliographic revision, based the concept of innovation management employed by leading organizations, called Open Innovation. The study has shown that Embrapa Coastal Tablelands had jointly developed 23 cultivars with other Embrapa Units. The hybrids were disregarded as part of the results, being counted in only to encompass the totals of cultivar development, as well as to update the Unit´s product catalogue. It has been concluded that the partnership among Units has made it possible to empower the initiatives for technology transfer by the partner Units in the region of the Coastal Tablelands, as well as to enhance vegetable genetic improvement programs and to introduce in the production systems materials which are more adaptable to the Brazilian Northeast soil and climate conditions.